2001
DOI: 10.1055/s-2001-15307
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Papillary Balloon Dilation vs. Sphincterotomy for Removal of Common Bile Duct Stones: A Prospective Randomized Pilot Study

Abstract: The results of this prospective randomized pilot study indicate that EST is superior to EBD in terms of stone removal, duration of the procedure, and complication rates. EST will therefore continue to be the standard procedure for stone removal in the near future. Further studies will be needed in order to compare the longer-term results with EST and EBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(64 citation statements)
references
References 12 publications
(39 reference statements)
2
57
0
5
Order By: Relevance
“…While endoscopic sphincterotomy involves cutting and carries bleeding rates of 2% to 5%, balloon dilatation theoretically preserves the biliary sphincter with reported no bleeding and consequently balloon dilatation has shown to be safe even in patients with coagulopathies who normally carry a 6.6% to 14.3% mortality rate with endoscopic sphincterotomy. This is also in agreement with Arnold et al and Lin et al who found higher bleeding rates among ES group involving 26% and 7% respectively and 1.9% and 0% in EBD group respectively [14,15].…”
Section: Discussionsupporting
confidence: 82%
“…While endoscopic sphincterotomy involves cutting and carries bleeding rates of 2% to 5%, balloon dilatation theoretically preserves the biliary sphincter with reported no bleeding and consequently balloon dilatation has shown to be safe even in patients with coagulopathies who normally carry a 6.6% to 14.3% mortality rate with endoscopic sphincterotomy. This is also in agreement with Arnold et al and Lin et al who found higher bleeding rates among ES group involving 26% and 7% respectively and 1.9% and 0% in EBD group respectively [14,15].…”
Section: Discussionsupporting
confidence: 82%
“…However, major limitations of EBD exist, including difficulty in removing large stones and a high incidence of pancreatitis. Since balloon dilation does not enlarge the sphincter of Oddi to the same extent as EST, large stone removal with EBD is difficult, and mechanical lithotripsy is required more often than with EST [11,21] . As a result, there is a need to modify the EBD technique to remove large bile duct stones and reduce the risk of pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…It has similar outcomes for common bile duct stone removal compared to EST, and has the advantages over EST of preserving papillary sphincter function and causing minimal complications such as hemorrhage and perforation [11][12][13][14][15][16][17][18][19] . Despite these advantages, EBD is associated with more severe and frequent occurrence of pancreatitis [20][21][22] . In addition, EBD has some technical difficulties for removing large stones because the biliary opening is not enlarged to the same degree as with EST [23] .…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled trial of treatment of bile duct stones involving 337 patients in the United States, pancreatitis occurred in 15.4% (5.1% severe) after balloon dilation vs 0.8% (none severe) after pull-type sphincterotomy (P < 0.01), with two deaths from severe pancreatitis after balloon dilation [48] . A study from Germany also found a high rate of pancreatitis after papillary balloon dilation [49] . Recommendations.…”
Section: Endoscopic Sphincterotomy (Es)mentioning
confidence: 99%